2013
DOI: 10.11599/germs.2013.1031
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in HIV-positive patients

Abstract: Conclusion An important aspect of this study is that both major risk factors identified are modifiable to an extent, and while cholesterol levels can be controlled with lipid-lowering medication, smoking can be stopped with or without replacement therapy. We need to stress on the importance of smoke-reducing policies and, particularly, encouraging young patients to not start smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
0
1
0
1
Order By: Relevance
“…International guidelines recommend evaluation and adjustment of common cardiovascular risk factors for all HIV-positive patients. As antiretroviral (ARV) drugs associate different profiles regarding the CV risk [2], the therapeutic regimens need to be managed on a case-by-case basis [3,4]. The prevalence of CV disease appears to be higher in the HIV population, compared to the general population, and recent studies have demonstrated that the supplementary risk for acute myocardial infarction in HIV-infected patients is 75% [5].…”
Section: Introductionmentioning
confidence: 99%
“…International guidelines recommend evaluation and adjustment of common cardiovascular risk factors for all HIV-positive patients. As antiretroviral (ARV) drugs associate different profiles regarding the CV risk [2], the therapeutic regimens need to be managed on a case-by-case basis [3,4]. The prevalence of CV disease appears to be higher in the HIV population, compared to the general population, and recent studies have demonstrated that the supplementary risk for acute myocardial infarction in HIV-infected patients is 75% [5].…”
Section: Introductionmentioning
confidence: 99%
“…Muitos estudos nacionais e internacionais adotam o ERF por ser um importante preditor para avaliação do risco de doença cardiovascular na população estudada (CIOE et al, 2014;DAGLAN et al, 2013;ECKARD et al, 2014;;FALCÃO et al, 2012;GLASS et al, 2006;VILELA et al, 2011).…”
Section: Instrumento Para Avaliação Da Alimentação Saudávelunclassified